Outbreak of Lumpy skin disease in India 2022- an emerging threat to livestock & livelihoods - Elavarasan Mathivanan; Kavitha Raju; Rajaganapathy Murugan (University of New South Wales, 2023)
An ongoing outbreak of Lumpy skin disease (LSD) has affected many states in India since May 2022. The disease originated in Zambia in 1929. The disease first appeared in South Asia in July 2019, with Bangladesh reporting an outbreak. India reported its first ever Lumpy skin disease outbreak in August 2019. LSD is a contagious epizootic disease caused by the Capri pox virus, which spreads among cattle. The major mode of transmission is vector-borne. There is no specific treatment for LSD. The current preventive measure include vaccination, movement control of bovine animals and quarantining, implementing biosecurity through vector control. There is no evidence that it can affect humans. The current outbreak in India has a wide range of morbidity rates, and higher range of mortality rates among cattle, comparing to the previous outbreak. The outbreak has resulted in huge economic implications for dairy farmers, which is exacerbated by the spread of misinformation through social media.